TGFβ-signaling in Squamous Cell Carcinoma Occurring in Recessive Dystrophic Epidermolysis Bullosa. (2011) - Knaup, Julia; Gruber, Christina; Krammer, Barbara; Ziegler, Verena; Bauer, Johann; Verwanger, Thomas
Abstract : Background : Recessive dystrophic epidermolysis bullosa (RDEB) is a hereditary skin disorder characterized by mechanical fragility of the skin, resulting in blistering and chronic wounds. The causative mutations lie in the COL7A1 gene. Patients suffering from RDEB have a high risk to develop aggressive, rapidly metastasizing squamous cell carcinomas (SCCs). Cutaneous RDEB SCCs develop preferentially in long-term skin wounds or cutaneous scars. Albeit being well differentiated, they show a more aggressive behavior than UV-induced SCCs. These findings suggest other contributing factors in SCC tumorigenesis in RDEB. Objective : To analyze factors contributing to RDEB tumorigenesis, we conducted a comprehensive gene expression study comparing a non-malignant RDEB (RDEB-CL) to a RDEB SCC cell line (SCCRDEB4) to achieve an overview on the changes of the gene expression levels in RDEB related skin cancer. Methods : We applied cDNA arrays comprising 9738 human expressed sequence tags (EST) with various functions. Selected results were verified by Real-time RT PCR. Results : Large-scale gene expression analysis revealed changes in the expression level of transforming growth factor β1 (TGFβ1) and several genes under the control of TGFβ for RDEB and SCCRDEB4 cell lines. Even untransformed RDEB keratinocytes show elevated levels of TGFβ1. Conclusion : Our findings demonstrate a prominent role of TGFβ-signaling in RDEB-related skin cancer. Once activated, TGFβ signaling either in response to wounding or in order to influence type VII collagen expression levels could facilitate cancer development and progression. Moreover, TGFβ signaling might also represent a potentially useful therapeutic target in this disease.